Closed Formulas for Some New Degree Based Topological Descriptors Using M-polynomial and Boron Triangular Nanotube - Shin, Dong Yun; Hussain, Sabir; Afzal, Farkhanda; Park, Choonkil; Afzal, Deeba; Farahani, Mohammad R. (Frontiers in Chemistry, 2021)
In this article, we give new formulas to compute the reduced reciprocal randic index, Arithmetic geometric index, SK index, SK1 index, SK2 index, edge version of first zagreb index, sum connectivity index, general sum connectivity index and forgotten index by using the M-polynomial and find these topological indices for a boron triangular nanotube. We also elaborate the results with graphical representation.